(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article examines the revival of folklore elements in Uzbek literature of the 20th century, with a particular focus on how traditional oral forms were artistically reimagined in modern literary texts. The study analyzes how writers utilized folklore such as myths, epics, legends, proverbs, and symbols to preserve national identity, convey cultural memory, and respond to social-political changes during the Soviet and post-Soviet eras. Through close textual analysis of works by Abdulla Qodiriy, Oybek, Gʻafur Gʻulom, Oʻtkir Hoshimov, and Erkin A’zam, the article demonstrates how folklore motifs were adapted to modern themes and genres. It also explores the stylistic and ideological significance of folkloric references in developing narrative voice, national consciousness, and moral discourse. Special attention is paid to the dual function of folklore as both a literary device and a cultural strategy to maintain continuity amidst rapid modernization and political suppression. The findings suggest that folklorization of literature played a crucial role in shaping the aesthetics and identity of 20th-century Uzbek prose.